OPTIMIZING POSTOPERATIVE OUTCOMES: ASSESSING THE EFFECT OF ENHANCED RECOVERY AFTER SURGERY PROTOCOLS IN GENERAL SURGICAL PATIENTS - Atif Iqbal,; Hamid ur Rehman,; Ibrar Ahmad,; Sauda Bibi,; Haseena Safdar,; Liaqat Ali,; Qazi Mohammad Hameed, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Enhanced Recovery After Surgery (ERAS) protocols were progressively implemented to advance postoperative results in various surgical specialties. However, their effectiveness in general surgical patients remains underexplored. This study intended to assess impact of ERAS protocols on postoperative results in general surgical patients at Jinnah International Hospital Abbottabad (JIHA). Methods: A retrospective cohort study was conducted at Jinnah International Hospital Abbottabad from May 2023 to April 2024. A total of 120 general surgical patients who underwent procedures under ERAS protocols were related with a historical control group who received conventional perioperative care. Data on perioperative variables, postoperative complications, length of hospital stay, and readmission rates were collected and analyzed. Results: Implementation of ERAS protocols resulted in significantly decreased postoperative complications (p < 0.05), shorter length of hospital stay (p < 0.001), and lower readmission rates (p < 0.01) compared to conventional perioperative care. Patients in the ERAS group experienced improved recovery trajectories and enhanced overall postoperative outcomes. Conclusion: The results of the study demonstrate beneficial impact of implementing ERAS protocols in general surgical patients at Jinnah International Hospital Abbottabad. Adoption of ERAS protocols can lead to enhanced postoperative recovery, reduced complications, and shorter hospital stays, ultimately optimizing patient outcomes.